Profiling Phenolic Composition in Pomegranate Peel From Nine Selected Cultivars Using UHPLC-QTOF-MS and UPLC-QQQ-MS - Man, Guowei; Xu, Lei; Wang, Yongtao; Liao, Xiaojun; Xu, Zhenzhen (Frontiers in Nutrition, 2022)
Pomegranate is widely cultivated across China and the phenolics in its peel are principal components associated with health benefits. Ultra-high performance liquid chromatography coupled to a quadrupole time-of-flight mass spectrometer (UHPLC-QTOF-MS) and ultra-performance liquid chromatography coupled to a triple quadrupole mass spectrometer (UPLC-QQQ-MS) were used in this study, aiming at profiling the total phenolic composition in pomegranate peel from 9 selected cultivars in 7 production areas. Sixty-four phenolic compounds were identified or annotated, and 23 of them were firstly reported in pomegranate peel. PCA plots show differences and similarities of phenolics among nine cultivars. Furthermore, fifteen phenolic compounds were quantified with the standards, and punicalagin, ellagic acid, gallocatechin, punicalin, catechin, corilagin were found to be dominant. Punicalagin weighed the highest content (28.03 mg/g to 104.14 mg/g). This study can provide a deeper and more detailed insight into the phenolic composition in pomegranate peel and facilitate health-promoting utilization of phenolics.